Impacts of livestock grazing on vegetation characteristics and soil chemical properties of alpine meadows in the eastern Qinghai-Tibetan Plateau. Issue 2 (2nd April 2020) - Ji, Lei; Qin, Yan; Jimoh, Saheed Olaide; Hou, Xiangyang; Zhang, Na; Gan, Youmin; Luo, Yuanjia
ABSTRACT: Livestock grazing is one of the significant causes of land degradation. However, the effect of contrasting grazing intensities on soil properties and vegetation in the southeastern Qinghai-Tibetan Plateau (QTP) is poorly understood. We studied the impact of light grazing (LG), moderate grazing (MG), heavy grazing (HG) and no grazing (NG) on vegetation characteristics and the chemical properties of soil samples taken at 0–10 cm, 10–20 cm and 20–30 cm layers from the designated grazing treatments. A total of 42 species representing 32 genera and 16 families were identified. Our result shows that HG significantly reduced total aboveground biomass, vegetation cover, canopy average height, but increased unpalatable aboveground biomass. Soil organic matter declined with increasing grazing intensity and respectively decreased to 64.51%, 65.38% and 82.40% for LG, MG and HG compared to the NG treatment and soil carbon storage exhibited a similar pattern. Soil total nitrogen and phosphorus contents decreased with increasing soil depth, while soil total potassium was not affected by grazing across soil depths. We conclude that 1 yak would have a more severe impact than 3 sheep units on the vegetation community and soil characteristics of alpine meadows in the southeastern QTP.